The Effect of Implementing Muamalah Principles and Sharia Accounting Literacy on the Financial Performance of MSMEs with Sharia Compliance as an Intervening Variable (A Study of MSMEs in Medan Petisah) - Mahyudin, Mahyudin; Muda, Iskandar; Soemitra, Andri; Yusrizal, Yusrizal (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the effect of implementing muamalah principles and Sharia accounting literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs), with Sharia compliance as an intervening variable. The research was conducted among MSME actors in the Medan Petisah subdistrict, involving 322 respondents selected using the Slovin formula. Data analysis employed Structural Equation Modeling with a Partial Least Squares (SEM-PLS) approach. The results show that the implementation of muamalah principles has a significant positive effect on financial performance but a negative effect on Sharia compliance. In contrast, Sharia accounting literacy has a direct negative effect on financial performance but contributes positively to Sharia compliance. Sharia compliance itself has a very strong influence on improving the financial performance of MSMEs. Path analysis reveals that Sharia compliance significantly mediates the relationship between both independent variables and financial performance. The mediation is competitive in the case of muamalah principles and complementary in the case of Sharia accounting literacy. These findings imply the importance of integrating Islamic values with structured Sharia compliance systems and institutional support to develop a sustainable Sharia-based MSME business model.